Discontinuation of treatment and retreatment of neovascular age-related macular degeneration in the real-world: Bundang AMD cohort study report 5 - Cho, Soo Chang; Park, Kyu Hyung; Park, Sang Jun; Joo, Kwangsic; Woo, Se Joon (Frontiers in Medicine, 2023)
Introduction This single-center retrospective cohort study investigated the incidence rate and risk factors for the discontinuation of anti-vascular endothelial growth factor (VEGF) injections and retreatment in typical neovascular age-related macular degeneration (tnAMD) and polypoidal choroidal vasculopathy (PCV) in the real-world setting. Methods A total of 488 eyes with either tnAMD (n = 334) or PCV (n = 154) followed up for ≥3 years were analyzed. The discontinuation of treatment was defined as the cessation of anti-VEGF injections for 1 year or longer. Eyes with discontinuing treatment were subdivided into group A: eyes with stable responses (complete or incomplete resolution) and group B: those with no expectation of visual gain or poor response. The proportion and median time of discontinuation of treatment or retreatment were analyzed. The visual prognosis and the associated risk factors for the discontinuation of treatment or retreatment were also investigated. Results The mean follow-up period was 8.1 ± 3.4 years. Of 488 eyes, discontinuation of the treatment occurred in 322 eyes (66.0%), and the median time to discontinuation was 1.5 years after the initial injection. Of 297 eyes with discontinuation of treatment excluding 25 eyes with vitrectomy or photodynamic therapy after the discontinuation of the injection, 277 eyes belonged to group A and the remaining 20 eyes belonged to group B. Of the 277 eyes discontinuing treatment with a stable response, 185 eyes (66.8%) were given retreatment. The median time to retreatment was 3.3 years after the discontinuation of the injections. PCV and the lower annual number of injections were the significant factors associated with discontinuation. Younger age, male gender, and PCV were the significant factors for the retreatment. Conclusion Our long-term real-world study showed that two-thirds of eyes with neovascular age-related macular degeneration (nAMD) had the discontinuation of the anti-VEGF injections and two-thirds of eyes discontinuing treatment with stable responses experienced retreatment. Long-term follow-up and regular monitoring are needed to detect the recurrence.